2014
DOI: 10.1121/1.4869678
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and simulation of acoustic radiation force on a planar reflector

Abstract: The accurate calculation of the acoustic radiation force is important for ultrasonic application techniques. Usually, the acoustic radiation force can be divided into the near-field and the far-field force according to the ratio of the emitter-reflector distance to the wavelength. In this study, appropriate theories and methods are explored to simulate the far-field and the near-field acoustic radiation force exerted on a planar reflector. The comparison between simulation and experiment indicates that the far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…This higher-order effect, not considered here, could be incorporated into the analysis, providing a small relative correction, of order δ ∼ ε, to the force experienced by the disk. The variation of Pe with α 2 corresponding to the piston-wall geometry is represented in figure 4(a) for selected values of St. As can be seen, Pe is always negative, which indicates that the time-averaged pressure near the entrance of the gas film is always smaller than the ambient value, with the magnitude of the pressure drop becoming larger for larger values of St. As demonstrated by the results shown in figure 4(b) for St = 5, the dependence of Pe on the geometrical configuration is fairly weak, well in qualitative accordance with the experimental observations of Hong et al (2014). The curves corresponding to the piston-piston and piston-wall configurations are nearly indistinguishable, while that for the disk-wall geometry exhibits departures of little over 5 % from the other two curves.…”
Section: Pressure Drop Across the Edge Regionsupporting
confidence: 83%
“…This higher-order effect, not considered here, could be incorporated into the analysis, providing a small relative correction, of order δ ∼ ε, to the force experienced by the disk. The variation of Pe with α 2 corresponding to the piston-wall geometry is represented in figure 4(a) for selected values of St. As can be seen, Pe is always negative, which indicates that the time-averaged pressure near the entrance of the gas film is always smaller than the ambient value, with the magnitude of the pressure drop becoming larger for larger values of St. As demonstrated by the results shown in figure 4(b) for St = 5, the dependence of Pe on the geometrical configuration is fairly weak, well in qualitative accordance with the experimental observations of Hong et al (2014). The curves corresponding to the piston-piston and piston-wall configurations are nearly indistinguishable, while that for the disk-wall geometry exhibits departures of little over 5 % from the other two curves.…”
Section: Pressure Drop Across the Edge Regionsupporting
confidence: 83%
“…2, n is the normal unit vector pointing outward from the surface S 0 . With a procedure similar to that adopted by Hong et al, 64 Eq. (2) is also used to obtain the acoustic radiation force acting on the reflector as a function of H.…”
Section: Numerical Modelmentioning
confidence: 99%
“…19,20) When the distance between an ultrasound vibrating plate and a planer object is much smaller than the ultrasound wavelength, the levitation force and the rigidity are dramatically increased (near-field acoustic levitation). [21][22][23][24][25] Ito reported that the radiation impedance of an ultrasound transducer varies with the ambient environment 26) and depends on the position of the reflector in the acoustic field, 27) implying that this phenomenon can be applied to acoustic touchless sensors.…”
Section: Introductionmentioning
confidence: 99%